China's one belt, one road initiative: what is it? Why? How? and potential implications - Hossain, Ishtiaq (2015)
This talk discussed the main features of China's One Belt and One Road Initiative. It also analyses and reasons for China to launch such a policy. The implications of such a policy on Southeast Asia is also discussed.